PIJ Property Development Sdn. Bhd. / Farhana Mod Noh - Mod Noh, Farhana (Universiti Teknologi MARA, Sarawak, 2016)
PIJ Property Development Sdn. Bhd. (formerly known as Perisind Property Development Sdn. Bhd.) was incorporated on 14th November 1994 as a Bumiputera private limited company having its registered office at Level 8, Bangunan PIJ Holdings, No.8, Jalan Bukit Timbalan, 80000 Johor Bahru, Johor. The main objectives of the Company are to be a reputable property developer and project management consultancy. PIJ Holdings Sdn wholly owns PIJPDSB. Bhd. (formerly known as Perisind Holdings Sdn. Bhd.), a business arm of Perbadanan Islam Johor. The Company has gone a long way since its incorporation both regarding the accumulation of work experience and capital accretion while maintaining a 100% Bumiputera equity participation. PIJPDSB will strive as one of the corporate institutions that move actively to develop few sectors such as property development and industrial area in Johor. This is correspondent with the objective of Johor 2005 development plan. While developing some area and modern city, the environmental aspects are also emphasizing thru the concept of town in a park and town forest. For example, the development at Ponderosa, which integrates the modern living concept and safety factors are adopted.